The Influence of Health Literacy and Social Support on Loneliness Among Patients With Severe Mental Illness in Rural Southwest China - Liu, Yan; Meng, Hongdao; Conner, Kyaien O; Qiao, Mutian; Liu, Danping (Frontiers in Psychology, 2021)
Loneliness is an important risk factor for poor health outcomes among adults, especially among those with severe mental illnesses (SMIs). Existing research has shown that adults with SMIs often lack health literacy, which contributes to more restricted social networks and low levels of social support. The objective of this cross-sectional study was to examine the influence of health literacy and social support on the loneliness of patients with SMI in rural Southwest China. We recruited 300 patients with SMI in rural Southwest China between December, 2017 to May, 2018 via a multi-stage stratified random sampling approach. We used structural equation modeling (SEM) test the hypothesized relationships among the variables of the 270 patients who completed the survey. Results of the SEM showed that health literacy was both directly and indirectly associated with loneliness, with social support playing a mediating role. These findings suggest psychoeducation for SMI patients, and their informal caregivers, may offer beneficial effects toward reducing loneliness in this vulnerable population.Further, social support is another potential target for intervention development for improving patient outcomes.